New Direct Assay of Free Protein S Antigen Applied to Diagnosis of Protein S Deficiency - Aillaud, M F; Pouymayou, K; Brunet, D; Alessi, M C; Amiral, J; Juhan-Vague, I (Thrombosis and Haemostasis, 1996)
Congenital deficiencies of protein S (PS) are associated with thrombophilia. Their characterization and classification have been hampered by the complex physiology of the protein C-protein S system and the poor standardization and reliability of laboratory assays. The free active form of protein S is usually determined by immunoassay using polyclonal antibodies in the plasma supemate after polyethyleneglycol (PEG) precipitation. A new one step ELISA using two monoclonal antibodies specific for distinct epitopes of the free form of protein S has been developed for the direct measurement of free PS in untreated plasma.We have tested two ELISA assays for free PS. One assay was based on the PEG precipitation (Asserachrom PS®, Stago, Asnières, France) whereas the other was a one step ELISA assay (Asserachrom® free PS, Stago). Values were obtained in 35 PS deficient patients recruited among 500 consecutive patients evaluated by the laboratory for diagnosis of congenital disorders of coagulation. Values were compared to those obtained in 50 patients with no PS deficiency matched for age and sex with the PS deficient patients as well as in 33 normal subjects and in 12 pregnant women. Strong correlation was found between the two tests (r = 0.81, p<10-5) in the entire population (n = 130), as well as in the separate groups. The new one step ELISA was more accurate than the PEG free PS determination. Determination of PS activity and antigens allowed us to separate quantitative and qualitative deficiencies. Among the qualitative deficiencies, isolated decrease in PS activity was the most frequent defect observed (66%). This fact questions the substitution of PS activity assays by the one step antigenic free PS ELISA assay.